Access to Health Insurance and Utilization of Substance Use Disorder Treatment: Evidence from the Affordable Care Act Dependent Coverage Provision. (27th January 2017) - Saloner, Brendan; Akosa Antwi, Yaa; Maclean, Johanna Catherine; Cook, Benjamin
Abstract: The relationship between insurance coverage and use of specialty substance use disorder (SUD) treatment is not well understood. In this study, we add to the literature by examining changes in admissions to SUD treatment following the implementation of a 2010 Affordable Care Act provision requiring health insurers to offer dependent coverage to young adult children of their beneficiaries under age 26. We use national administrative data on admissions to specialty SUD treatment and apply a difference‐in‐differences design to study effects of the expansion on the rate of treatment utilization among young adults and, among those in treatment, changes in insurance status and payment source. We find that admissions to treatment declined by 11% after the expansion. However, the share of young adults covered by private insurance increased by 5.4 percentage points and the share with private insurance as the payment source increased by 3.7 percentage points. This increase was largely offset by decreased payment from government sources. Copyright © 2017 John Wiley & Sons, Ltd.